The diversity paradox : immigration and the color line in twenty-first century America - Lee, Jennifer, 1968-; Bean, Frank D. (Russell Sage Foundation, 2010)
"Using an impressive arsenal of quantitative and qualitative data, Jennifer Lee and Frank Bean offer an authoritative analysis of the color line in American society, revealing a remarkable paradox at the heart of contemporary intergroup relations. Although immigration has dramatically increased the share of Asians and Latinos, and patterns of intermarriage and self-identification reveal greater racial and ethnic mixing than ever before, one divide continues to stand out: that between African Americans and everyone else. Their careful analysis challenges both glib assertions of a post-racial order as well as pronouncements about the immutability of America's racial categories. Racial meanings are clearly changing, but whether they will change enough to overcome the age-old `American Dilemma' remains to be seen."--Douglas S. Massey, Henry G. Bryant Professor of Sociology and Public Affairs, the Woodrow Wilson School.